Divorcing with children : expert answers to tough questions from parents and children - Lippman, Jessica G., 1941- (Praeger, 2008)
It's a sad reality but one we must face and understand for the children's sake. Each year, hundreds of thousands of parents separate or divorce, and their marital breakdown is most often heartbreaking, mystifying, and painful for their children. The youngsters, regardless of age, may or may not get honest, open explanations. They may or may not understand. Reasons for the breakdown aside, it is a loss for the children, something to grieve. Many parents make it more difficult by putting the children in the middle, or telling them things to alienate them against the other parent. The children le.